Análise de modelo matemático para simular a reação catalítica de conversão de CO2 a DME em leito fixo. - Carvalho, Aline Estevam (2021)
In view of the increasing levels of carbon dioxide emissions in the atmosphere and the climate changes resulting from such emissions, the development of novel processes that allow the reduction of the CO2 levels in the atmosphere has been encouraged. In addition, CO2 has been studied as a possible source of added-value carbon, allowing its capture and conversion into energetically valuable products. Considering the actual scenario of the carbon capture and utilization technologies, a pseudo homogeneous mathematical model was implemented to describe and simulate the behavior of the DME production in fixed bed reactor by CO2 direct conversion. The proposal of the model, therefore, allows to evaluate the formation of DME from a feed composed exclusively of CO2 and H2, indicating the feasibility of the process and the best adjustment of the defined parameters. This reactional process was simulated in gPROMS® software using kinetic models commonly adopted for CuO-ZnO-Al2O3 catalysts supported in γ-Al2O3. The mathematical model was validated by experimental data reported in literature for CO2 conversion in DME. The experiments were conducted in a fixed bed reactor, operated at 40 bar pressure and 275 °C. A series of analysis was made in function of operational parameters such as temperature, pressure, feed composition and space velocity. The results show the improvement of DME production from CO2 conversion with the presence of CO in the feed composition for CO/CO2 of 0.05, 0.08 and 0,1. In ratios (H2/CO+CO2) = 3, 20 bar pressure and 280 ºC, and 1000 mL g-1 h-1, CO2 conversion reached 19,.15%, with 17,.6% and 7,.4% of methanol and dimethyl ether yield, respectively. The water presence in the process was undesirable, interfering on the DME productivity. Future works aiming the reduction or removal of the water in the process can be developed to promote the DME production.